Bioaccumulation and biomagnification of halogenated organic pollutants in mangrove biota from the Pearl River Estuary, South China. Issue 1 (15th October 2015) - Sun, Yu-Xin; Zhang, Zai-Wang; Xu, Xiang-Rong; Hu, Yong-Xia; Luo, Xiao-Jun; Cai, Ming-Gang; Mai, Bi-Xian
Highlights: PCBs, DDTs, PBDEs, DP and DBDPE were detected in mangrove biota from the PRE. Interspecific differences in HOPs levels were found among mangrove biota species. DDTs were the predominant HOPs in mangrove biota, followed by PCBs and PBDEs. Biomagnification potentials for HOPs were observed in mangrove food webs. Abstract: Four biota species were collected from mangrove ecosystems of the Pearl River Estuary to investigate the bioaccumulation and biomagnification of polychlorinated biphenyls (PCBs), dichlorodiphenyltrichloroethane (DDT), polybrominated diphenyl ethers (PBDEs), dechlorane plus (DP), and decabromodiphenyl ethane (DBDPE). Concentrations of ΣPCBs, ΣDDTs, ΣPBDEs, DP, DBDPE and anti -Cl11 -DP (the dechlorination product of anti -DP) in mangrove biota ranged from 32.1–466, 153–3819, 3.88–59.8, 0.18–6.88, not detected (nd)–30.6 and nd–2.65 ng/g lipid weight, respectively. Daggertooth pike conger ( Muraenesox cinereus ) had higher concentrations of contaminants than the other three biota species. Significant positive relationship between anti -Cl11 -DP and anti -DP levels was observed in mangrove biota. DDTs were the predominant HOPs in all biota species, followed by PCBs and PBDEs. All the target compounds exhibited biomagnification, with biomagnification factors greater than 1 in the studied feeding relationships. Food web magnification was found for ΣPCBs, ΣDDTs, ΣPBDEs and DP, with trophic magnification factors of 2.76, 2.61, 2.20 and 2.31, respectively.